Gingerbread cookie murder - Fluke, Joanne, 1943- (Kensington, 2010)
Hannah Swensen of the Cookie Jar in Lake Eden, Minn., discovers her neighbor's head bashed in; Jaine Austen's holiday stay at her parents' home in the Tampa Vistas retirement community is enlivened by the murder of elderly lothario; and, Maine reporter Lucy Stone investigates a four-year-old boy's disappearance. Includes recipes.